2017
DOI: 10.1016/j.jfda.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and quantification of polyphenols from kinnow ( Citrus reticulate L.) peel using ultrasound and maceration techniques

Abstract: An investigation was carried out to extract polyphenols from the peel of kinnow (Citrus reticulate L.) by maceration and ultrasound-assisted extraction (UAE) techniques. The antioxidant potential of these polyphenols was evaluated using ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and superoxide radical scavenging assays; and their antimicrobial activity was assessed against bacterial strains Staphyloccoccus aureus, Bacillus cereus, and Salmonella typhimurium. The highest ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
138
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(166 citation statements)
references
References 51 publications
19
138
0
9
Order By: Relevance
“…Zhang et al (2018) have found that TFC for Chinese C. reticulata methanolic extracts ranged from 23.29 to 56.52 mg RE/g, which was evidently higher compared to our results (6.34-8.05 mg QE/g). Generally, literature data demonstrate that the TPC and TFC vary depending on the locality, season, applied solvent and the extraction procedure (Javanmardi et al, 2003;Kivrak et al, 2017;Muñiz-Márquez et al, 2014;Safdar et al, 2017). In our study ( Table 1) the statistical analysis showed that the sample origin had a significant influence on both TPC and TFC.…”
Section: Yields Total Phenolic and Flavonoid Contents Of Extractssupporting
confidence: 52%
“…Zhang et al (2018) have found that TFC for Chinese C. reticulata methanolic extracts ranged from 23.29 to 56.52 mg RE/g, which was evidently higher compared to our results (6.34-8.05 mg QE/g). Generally, literature data demonstrate that the TPC and TFC vary depending on the locality, season, applied solvent and the extraction procedure (Javanmardi et al, 2003;Kivrak et al, 2017;Muñiz-Márquez et al, 2014;Safdar et al, 2017). In our study ( Table 1) the statistical analysis showed that the sample origin had a significant influence on both TPC and TFC.…”
Section: Yields Total Phenolic and Flavonoid Contents Of Extractssupporting
confidence: 52%
“…They concluded that that 50% acetone yielded the highest content of polyphenols compared to methanol, ethanol, ethyl-acetate and hexane. Safdar et al (2016) extracted and quantified polyphenols from kinnow (Citrus reticulate L.) peel. Maximum polyphenols were extracted with 80% methanol (32.48 mg GAE/g extract) using ultrasound assisted extraction, whereas, minimum phenolics (8.64 mg GAE/g extract) were obtained with 80% ethyl acetate through the maceration technique.…”
Section: Solvent Extraction Techniquementioning
confidence: 99%
“…Our results are in accordance with those in peel of sweet orange as reported by Wang et al (). Other studies have also reported similar effect of sample matrix, extraction method, and processing conditions on the individual phenolic release and their content (Safdar et al, ). In a study on UAE of polyphenolics from sweet orange peel, showed presence of naringin (70.30 mg/100 g wb) and hesperidin (205.20 mg/100 g wb), later being the predominant compound (Khan et al, ).…”
Section: Resultsmentioning
confidence: 59%